2021
DOI: 10.3390/ijms22179297
|View full text |Cite
|
Sign up to set email alerts
|

Development, Diversity, and Death of MGE-Derived Cortical Interneurons

Abstract: In the mammalian brain, cortical interneurons (INs) are a highly diverse group of cells. A key neurophysiological question concerns how each class of INs contributes to cortical circuit function and whether specific roles can be attributed to a selective cell type. To address this question, researchers are integrating knowledge derived from transcriptomic, histological, electrophysiological, developmental, and functional experiments to extensively characterise the different classes of INs. Our hope is that suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 267 publications
(341 reference statements)
0
19
0
2
Order By: Relevance
“…Though INs comprise only ∼20% of cortical neurons, they are the only GABAergic neurons in cortex, and are critical to regulating activity of cortical circuits through a variety of mechanisms ( Takada et al, 2014 ). This diversity of inhibitory signaling is mediated by a number of functionally distinct subtypes, such as parvalbumin (PV) and somatostatin (SST) INs, which have different birth origins ( Wonders and Anderson, 2006 ; Lim et al, 2018 ) and properties at maturity ( Markram et al, 2004 ; Kepecs and Fishell, 2014 ; Williams and Riedemann, 2021 ). Deficits in IN development and function underlie neurologic and psychiatric disorders, such as epilepsy ( Bozzi et al, 2012 ; Righes Marafiga et al, 2021 ), schizophrenia, bipolar disorder, and autism spectrum disorders ( Rossignol, 2011 ; Marin, 2012 ; Ruden et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Though INs comprise only ∼20% of cortical neurons, they are the only GABAergic neurons in cortex, and are critical to regulating activity of cortical circuits through a variety of mechanisms ( Takada et al, 2014 ). This diversity of inhibitory signaling is mediated by a number of functionally distinct subtypes, such as parvalbumin (PV) and somatostatin (SST) INs, which have different birth origins ( Wonders and Anderson, 2006 ; Lim et al, 2018 ) and properties at maturity ( Markram et al, 2004 ; Kepecs and Fishell, 2014 ; Williams and Riedemann, 2021 ). Deficits in IN development and function underlie neurologic and psychiatric disorders, such as epilepsy ( Bozzi et al, 2012 ; Righes Marafiga et al, 2021 ), schizophrenia, bipolar disorder, and autism spectrum disorders ( Rossignol, 2011 ; Marin, 2012 ; Ruden et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Most cortical and hippocampal interneurons in mammals are derived from three different regions in the basal telencephalon: the MGE, CGE, and preoptic area ( Christodoulou et al, 2021 ). Approximately 60% of cortical interneurons are derived from the MGE, 30% from the CGE, and the remaining 10% from the preoptic area ( Williams and Riedemann, 2021 ). Inhibitory interneurons play a dominant role in maintaining the functional balance of neural circuits (as elaborated in the next section).…”
Section: Medial Ganglionic Eminence-derived Interneuronsmentioning
confidence: 99%
“…The balance between excitation and inhibition in the cortical neural circuits is maintained by GABAergic interneurons ( Wang et al, 2016 ). In animals and humans, interneuron loss or malfunctioning can result in mood disorders, working memory disorders, or cognitive decline ( Casalia et al, 2021 ; Williams and Riedemann, 2021 ), leading to epilepsy ( Knopp et al, 2008 ), Alzheimer’s Disease (AD) ( Fu et al, 2017 ; Najm et al, 2020 ), schizophrenia ( Dienel and Lewis, 2019 ; Van Derveer et al, 2021 ), autism spectrum disorder (ASD) ( Shin et al, 2021 ; Deemyad et al, 2022 ) and other neurological disorders. Researches have revealed that MGE-derived interneuron transplantation offers hope for treating these diseases ( De la Cruz et al, 2011 ; Perez and Lodge, 2013 ; Upadhya et al, 2019 ; Lu et al, 2020 ; Southwell et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Они описаны в неокортексе мышей, крыс, морских свинок, кроликов, кошек и обезьян, в основном вблизи границы между корой и белым веществом, с меньшим количеством в коре, в основном в поверхностных слоях (II-IV) [10,12]. По мнению Williams et al [15][16][17], у крыс эти нейроны в основном обнаруживаются в более глубоких слоях и экспрессируют nNOS на более высоких уровнях. Хотя нейроны nNOS 1-го типа получают множество различных нейромодулирующих сигналов [15,16], почти все они экспрессируют рецептор вещества P, причем как геномные, так и гистологические исследования показали, что это единственная субпопуляция клеток коры головного мозга мышей, которая экспрессируют этот рецептор [3,4,5,13,14].…”
Section: Introductionunclassified
“…По мнению Williams et al [15][16][17], у крыс эти нейроны в основном обнаруживаются в более глубоких слоях и экспрессируют nNOS на более высоких уровнях. Хотя нейроны nNOS 1-го типа получают множество различных нейромодулирующих сигналов [15,16], почти все они экспрессируют рецептор вещества P, причем как геномные, так и гистологические исследования показали, что это единственная субпопуляция клеток коры головного мозга мышей, которая экспрессируют этот рецептор [3,4,5,13,14]. Нейроны nNOS-IR 1-го типа имеют протяженные отростки, которые позволяют им влиять на сосудистую сеть.…”
Section: Introductionunclassified